2011
DOI: 10.5326/jaaha-ms-5627
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Prostatitis, Cystitis, Pyelonephritis, and Balanoposthitis in a Cat

Abstract: An adult, intact male domestic shorthair presented for preputial swelling and urinary incontinence. A caudal abdominal mass was palpated. A transabdominal ultrasound examination showed severe prostatomegaly with abnormal tissue extending along the urethra. The cat was euthanized due to the owner's financial constraints and the veterinarians' suspicion of a poor long-term prognosis. Biopsies showed chronic active inflammation of the prostate, bladder, kidneys, ureters, penis, and prepuce most consistent with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 8 publications
0
9
1
Order By: Relevance
“…In our series of cats, UI was associated with a variety of congenital and acquired disorders that affected both phases of micturition with similar frequency. The proportional morbidity of causes, sex, age distribution, and outcomes of UI in our series of cats differed substantially from previous reports of UI in cats and dogs . Our observations indicated that spinal cord disorders were a common cause of UI in cats and were associated with less favorable outcomes compared to bladder and urethral disorders.…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…In our series of cats, UI was associated with a variety of congenital and acquired disorders that affected both phases of micturition with similar frequency. The proportional morbidity of causes, sex, age distribution, and outcomes of UI in our series of cats differed substantially from previous reports of UI in cats and dogs . Our observations indicated that spinal cord disorders were a common cause of UI in cats and were associated with less favorable outcomes compared to bladder and urethral disorders.…”
Section: Discussioncontrasting
confidence: 85%
“…Diagnoses included urethral stricture, urethral stents, urethritis, congenital and acquired USMI, congenital urethral hypoplasia, post‐perineal urethrostomy, and undetermined urethral dysfunction, all of which have been reported previously . Other reported urethral disorders associated with UI in cats include urethral diverticulum, prostatitis, prostatic neoplasia, reflex dyssynergia, and epidural analgesia . Urethral diseases were significantly more common in males, most likely because of increased frequency of iatrogenic injury occurring secondary to perineal urethrostomy (5 cats) or urethral catheterization (2 cats), which has been reported previously .…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…1,2,[5][6][7][8] The prostate gland surrounds the pelvic urethra, beginning at the level of the trigone of the urinary bladder. Pathologic conditions are fairly common in the dog although rarely reported in cats.…”
Section: Normal Prostate Glandmentioning
confidence: 99%
“…However, in cats, ultrasonography is less described as a diagnosis method due to the rare condition of some reproductive changes. Some reports describe the occurrence of prostatic diseases, such as neoplasms, para-prostatic cysts and prostatitis (Pointer and Murray, 2011).…”
Section: Testicular Abnormalities B-mode Ultrasoundmentioning
confidence: 99%